Pengaruh Motivasi Kerja Perawat Ruang Rawat Inap terhadap Pelaksanaan Ronde Keperawatan di Rumah Sakit Umum Daerah Bajawa - Gabriela Deviana Mamo; Rina Waty Sirait; Dominirsep O. Dodo (SEHATMAS: Jurnal Ilmiah Kesehatan Masyarakat, 2026)
Nursing rounds are one of the important methods to improve the quality of nursing services in hospitals, especially in enhancing communication among nurses and optimizing patient care. However, the implementation of nursing rounds at Bajawa Regional General Hospital has not been carried out optimally, which is suspected to be influenced by low nurse work motivation. This study aims to determine the influence of nurses’ work motivation in inpatient wards on the implementation of nursing rounds at Bajawa Regional General Hospital. This study used a quantitative method with a cross-sectional approach. The population consisted of 108 nurses working in inpatient wards, with a sample of 51 respondents selected using simple random sampling. Data were collected through questionnaires and analyzed using the Chi-Square test. The results showed that most nurses had high work motivation (84.3%) and implemented nursing rounds (94.1%). Statistical analysis showed a significant relationship between work motivation and the implementation of nursing rounds (p = 0.012; OR = 0,071). There is a significant influence between nurses’ work motivation and the implementation of nursing rounds in inpatient wards at Bajawa Regional General Hospital. It is recommended that hospital management enhance nurses’ motivation through continuous support, recognition, and supervision to optimize nursing round implementation.